Geoarchaeological evidence of landscape degradation in the Valley of the Muses (Boeotia, Greece) during classical antiquity - Peña-Monné, José Luis; Sampietro-Vattuone, María Marta (Journal of Greek Archaeology, 2023)
At the foot of Mount Helicon, in Boeotia, Central Greece, is located the Valley of the Muses, traversed by the Askris River. The valley was known in the Antiquity as the location of the Sanctuary of the Muses, where every four years festivals (Mouseia) were held in honor of the muses. It was also the place of birth of the poet Hesiod. Therefore, even today it retains a special mythical appeal. At that time, the humidity provided by the mountain massif surrounding the valley should have helped to create an ideal landscape to stimulate poetic inspiration and literary and musical creativity. In the words of Pausanias ‘Helikon is one of the mountains of Greece with the most fertile soil and the greatest number of cultivated trees. The wild-strawberry bushes supply to the goats sweeter fruit than that growing anywhere else’. He also spoke of the existence of a ‘holly forest’ in the area of the Sanctuary. It is difficult to recognize this special environment at present at the head of the valley and on Mount Helicon, where the Muses Sanctuary was located and to imagine the magnetism of the area as a meeting point for such a particular artistic activity. This is because the imprint left by the complex process of subsequent human occupation of the area generated profound changes in the landscape of the valley, also extensive to nearby areas. Besides, only a few remains of the theater and the Sanctuary of the Muses as well as such ancient settlements of the surroundings, as Askra and Thespies, are lying under present crops or scrub. Much archaeological and geoarchaeological information about these historic sites and landscapes however has been recovered since 1978 due to the Boeotia Project directed by John Bintliff and Anthony Snodgrass.